2011
DOI: 10.1007/s00595-011-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Kampo medicine “Dai-kenchu-to” prevents CPT-11-induced small-intestinal injury in rats

Abstract: DKT suppressed CPT-11 induced inflammatory cytokines and apoptosis in the intestinal mucosa and maintained the mucosal integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…A prior study had shown that small intestinal damage induced by the drug CPT-11 is also inhibited by TU-100 [43]. Whether TU-100 can be used to treat other small bowel inflammatory diseases such as viral enteritis or Celiac disease remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study had shown that small intestinal damage induced by the drug CPT-11 is also inhibited by TU-100 [43]. Whether TU-100 can be used to treat other small bowel inflammatory diseases such as viral enteritis or Celiac disease remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, another combination treatment, which can block the cytotoxic effects of CPT-11 on normal cells, but not in tumor cells, should be sought. Various in vivo studies in animals and clinical trials in humans have reported that TU-100 shows multiple functions, including the downregulation of inflammatory mediators, with negligible side effects [13]. We therefore hypothesized that the addition of TU-100 Fig.…”
Section: The Expression Of Caspase-3 and The Tight Junction Proteinsmentioning
confidence: 98%
“…These include: anti-inflammatory properties through the selective inhibition of cyclooxygenase-2 (COX-2) 8) and/or down-regulation of several inflammatory mediators such as tumor necrosis factor-α, interleukin-1b and endothelin-1; prevention of bacterial translocation 9,10) ; and increased gastrointestinal blood flow through the induction of calcitonin gene-related peptide (CGRP), substance P, and vasoactive intestinal polypeptide (VIP) 11,12) .…”
mentioning
confidence: 99%